2012
DOI: 10.1002/j.1532-2149.2012.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Low back pain‐related beliefs and likely practice behaviours among final‐year cross‐discipline health students

Abstract: Aligning cross-discipline university curricula with current evidence may provide an opportunity to facilitate translation of this evidence into practice with a focus on a consistent, cross-discipline approach to LBP management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 45 publications
9
79
2
3
Order By: Relevance
“…A recent study showed that Australian physical therapy students had a total score of 40.2 on HC-PAIRS. 13 Although it was not significant, Burnett et al 17 found a higher HC-PAIRS total score in Singaporean (61.5) and Taiwanese (60.8) compared with Australian (57.8) physical therapy students. Briggs et al 13 found that physical therapy students reported more helpful beliefs than students from other disciplines, namely, chiropractic, medicine, occupational therapy, and pharmacy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A recent study showed that Australian physical therapy students had a total score of 40.2 on HC-PAIRS. 13 Although it was not significant, Burnett et al 17 found a higher HC-PAIRS total score in Singaporean (61.5) and Taiwanese (60.8) compared with Australian (57.8) physical therapy students. Briggs et al 13 found that physical therapy students reported more helpful beliefs than students from other disciplines, namely, chiropractic, medicine, occupational therapy, and pharmacy.…”
Section: Discussionmentioning
confidence: 92%
“…13 Although it was not significant, Burnett et al 17 found a higher HC-PAIRS total score in Singaporean (61.5) and Taiwanese (60.8) compared with Australian (57.8) physical therapy students. Briggs et al 13 found that physical therapy students reported more helpful beliefs than students from other disciplines, namely, chiropractic, medicine, occupational therapy, and pharmacy. Ferreira et al 14 reported that the Brazilian students and the Australian students in Latimer's study 6 had similar demographic characteristics, except that 22.2% of the Australian students had a previous degree (3.9%).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, it has been shown that unhelpful beliefs are associated with higher levels of pain and disability [21-24]. These beliefs can be influenced either positively or negatively by interactions with HCPs [25-27], which are in turn influenced by health professionals’ training, their clinical interests in the management of LBP and the beliefs held by the HCPs themselves [27-29]. …”
Section: Introductionmentioning
confidence: 99%
“…Results from a survey of 171 final year Australian physiotherapy students responding to a vignette describing a woman with acute LBP with no red flags were similar.62% of the students indicated they would recommend physical activity and 75% would recommend avoiding bed rest [18]. For vignette 5, where imaging was indicated for a suspected fracture, 79% of physiotherapists reported they would X-ray, and 32% reported they would refer to another practitioner.…”
Section: Discussionmentioning
confidence: 95%